2021
DOI: 10.3233/jnd-200617
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Adult Spinal Muscular Atrophy Outcome Measures Toolkit: Results of a National Consensus using a Modified Delphi Method

Abstract: Background: Spinal Muscular Atrophy (SMA) is a rare disease that affects 1 in 11 000 live births. Recent developments in SMA treatments have included new disease-modifying therapies that require high quality data to inform decisions around initiation and continuation of therapy. In Canada, there are no nationally agreed upon outcome measures (OM) used in adult SMA. Standardization of OM is essential to obtain high quality data that is comparable among neuromuscular clinics. Objective: To develop a recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Several domains must be evaluated, considering that the treatment is effective if the improvement is demonstrated in one or more of these domains: motor function, motor milestones, respiratory function, bulbar function (speech and swallowing), and nutritional data. 126 The SMArtCARE project is a platform to collect real-life outcomes data of patients with SMA in Germany, Austria, and Switzerland. It proposes standardized instruments to be used according to age and functional motor capacity (►Table 2).…”
Section: Real-world Assessment Of Therapeutic Efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…Several domains must be evaluated, considering that the treatment is effective if the improvement is demonstrated in one or more of these domains: motor function, motor milestones, respiratory function, bulbar function (speech and swallowing), and nutritional data. 126 The SMArtCARE project is a platform to collect real-life outcomes data of patients with SMA in Germany, Austria, and Switzerland. It proposes standardized instruments to be used according to age and functional motor capacity (►Table 2).…”
Section: Real-world Assessment Of Therapeutic Efficacymentioning
confidence: 99%
“…132,133 Consistent with the literature, there is poor availability of outcome measures for bulbar function. 126 Therefore, we suggest that the evaluation of therapeutic efficacy in this domain be done through the need for a nasogastric tube or gastrostomy, video fluoroscopy swallow study, or clinical assessment of the risk of aspiration. 131 Fatigue is a complex issue but a frequent complaint of SMA patients, especially in types 2 and 3.…”
Section: Real-world Assessment Of Therapeutic Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…The censuses were reached using 2 rounds of modified Delphi method. 61 Elsheikh et al conducted the 6MWT in 30 ambulatory adults with SMA and found that 97% of patients were able to complete the test, suggesting feasibility for assessment in the targeted population. 62 Construct validity was assessed using convergent validity in 3 studies in 65 ambulatory patients with type II and III SMA and ages ranging from 4 to 55.3 years.…”
Section: -Minute Walk Test (6mwt)mentioning
confidence: 99%